2021
DOI: 10.3390/brainsci11101321
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization Outcome Prediction for A Direct Aspiration-First Pass Technique (ADAPT) from Pre-Treatment Imaging and Machine Learning

Abstract: A direct aspiration-first pass technique (ADAPT) has recently gained popularity for the treatment of large vessel ischemic stroke. Here, we sought to create a machine learning-based model that uses pre-treatment imaging metrics to predict successful outcomes for ADAPT in middle cerebral artery (MCA) stroke cases. In 119 MCA strokes treated by ADAPT, we calculated four imaging parameters—clot length, perviousness, distance from the internal carotid artery (ICA) and angle of interaction (AOI) between clot/cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Nonetheless, first-pass complete reperfusion should be the goal of every MT procedure [31], since it is linked to a better clinical outcome, a lower mortality, and fewer procedural adverse events. This is probably related to the faster procedure time and to a minor risk of endothelial vascular trauma and its resulting complications [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, first-pass complete reperfusion should be the goal of every MT procedure [31], since it is linked to a better clinical outcome, a lower mortality, and fewer procedural adverse events. This is probably related to the faster procedure time and to a minor risk of endothelial vascular trauma and its resulting complications [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The mean or median ages of the study participants ranged from 64.0 to 86.0 years, and the proportion of male participants ranged from 35.0 to 65.9%. Only one US study ( 24 ) specifically described the self-reported ethnicity of the patients (63.0–69.0% European ancestry); the other studies reported the place of patient recruitment [USA: 1 ( 32 ); Europe: 10 ( 22 , 23 , 26 29 , 31 , 33 35 ); Asia: 4 ( 25 , 30 , 36 , 37 )]. The training sample sizes ranged widely, from 109 to 1,401.…”
Section: Resultsmentioning
confidence: 99%
“…Tree models ( 22 , 24 , 31 ), random forests ( 23 , 26 , 27 ), and support vector machines ( 28 , 30 , 33 ) were each proposed by three studies, regularized logistic regression by two studies ( 25 , 32 ), and artificial neural networks by one study ( 29 ). To accommodate missing values, two studies used multiple imputation ( 23 , 29 ) and one used singular imputation ( 31 ), while other studies excluded participants with missing data in either predictive or outcome variables (complete-case analysis) ( 22 , 24 28 , 30 , 32 , 33 ). The number of predictive variables used for model construction varied from 4 ( 32 ) to 53 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations